Digitalisasi Kenotariatan: Peluang Dan Tantangan Dalam Era Teknologi: DIGITALISASI KENOTARIATAN: PELUANG DAN TANTANGAN DALAM ERA TEKNOLOGI - Ibnatun Nafi, Naili; Adjie, Habib (Jurnal Media Justitia Nusantara, 2025)
Digitalization has become a global trend that has brought significant changes in various sectors, including the notary field. This study aims to analyze the opportunities and challenges of digitalization in notary practice in Indonesia, focusing on its impact on work efficiency, data security, document validity, and regulatory readiness. The research approach uses a mixed-method with a sequential explanatory design. Quantitative data was obtained through a survey of 150 respondents consisting of notaries, PPATs, and notary service users, while qualitative data was collected through in-depth interviews with practitioners, academics, and regulators. The results of the study show that digitalization presents great opportunities, such as increased efficiency through electronic signatures, blockchain-based document security, and the expansion of service access to remote areas. However, the challenges faced are no less significant. The disharmony between the Information and Electronic Transactions Law (ITE Law) and the Notary Position Law (UUJN) creates legal uncertainty regarding the validity of digital documents. In addition, the risk of data leakage and lack of technological literacy among notaries are the main obstacles in the implementation of digitalization. This study concludes that digital transformation in the notary sector requires harmonization of regulations, increasing the capacity of human resources, and strengthening technological infrastructure. Strategic recommendations include revision of legal policies, technology training for notaries, and investments in data security. With these steps, digitalization is expected to support notary practices that are more efficient, safe, and relevant to the needs of society in the technological era. This research provides important insights for regulators, notaries, and other stakeholders in welcoming the digital notary era.